Peran Digital Marketing, E-WOM, dan Kualitas Produk terhadap Keputusan Pembelian di Adhi Fashion Garment - Mandira, I Made Chandra; Korry, Putu Dyah Permatha; Parasari, Nyoman Sri Manik; Putra, I Dewa Gede Sanjaya (LPPM Universitas Bina Sarana Informatika, 2024)
Current study aimed to identify the role of digital marketing, E-WOM, and product quality on consumer purchasing decisions at Adhi Fashion Garment. The target population used is all residents of South Denpasar City who have purchased Adhi Fashion Garment products. Through a purposive sampling technique, 168 respondents were obtained who participated in filling out the questionnaire. Based on the results of calculations using PLS-SEM version 4.0 software, the results showed that digital marketing, electronic word of mouth (e-WOM) and product quality had a positive and significant influence on purchasing decisions at Adhi Fashion Garment, South Denpasar. The implications of the results of this research show that the better the implementation of digital marketing strategies and consumers' positive stories about their experiences using certain products, the more this can improve purchasing decisions. And the better the quality of the products offered, especially fashion products, will be able to improve consumer purchasing decisions.